The Effect of Sambiloto (Andrographis paniculata) Leaf Extract in Combination with Phosphomycin on The Germ Number, Urine Leukocyte Esterase, and Urine Procalcitonin Levels in Wistar Rats (Rattus norvegicus) Urinary Tract Infection Model - Hadinata, Sebastian; Lestari, Endang Sri; Nugroho, Eriawan Agung; Nindita, Yora; Addin, Sofyan Rais (Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Bacterial resistance to antibiotics is still common due to unwise use. Urinary Tract Infections (UTI), 80% ofwhich are caused by E. coli and other bacteria such as Enterobactersp, Klebsiellasp, S. aureus. Phosphomycin is a first-line antibiotic for UTI. Combining natural compounds with antibiotics is one treatment strategy to increase the effectiveness of anti-bacterialt herapy. Andrographispaniculata has been reported to have strong anti-infectiveactivity. This study aimed to prove the differences in the germ number, leukocyte esterase levels,and urine procalcitonin levels in Rattus norvegicus UTI model given the phosphomycin, Sambilotoleaf extract, and Sambiloto leaf extract-phosphomycin combination. Methods: Thirty Rattus novergicus rats were divided into five groups. All groups were induced 50 µl of E. coli bacterial inoculum for 7 days, followed by standard feed (negative control), fosfomycin (Monuril®) 54 mg (positive control), Sambilotoleaf extract (S1 [100 mg/BW], S2 [200 mg/BW],Sambiloto leaf extract-phosphomycin combination (FS1 [sambiloto 100 mg/BW and fosfomycin 54 mg], and FS2 [sambiloto200 mg/BW and phosphomycin 54 mg]) for the next 7 days orally.The germ number, leukocyte esterase, and urine procalcitonin were measured after all rats were given treatment. Results: The largest averagere duction in the germ number, levels of leukocyte esterase, and urinary procalcitonin (4.80 ± 3.70 CFU/ml [p<0.05], 3,00 ± 6,71 cells/µL [p<0.05], 4,66 ± 1,35 ng/L [p<0.05] respectively)was observed in the combination of 200 mg/BW Sambiloto leaf extract-phosphomycin combination group. Conclusion: A combination of Sambiloto leaf extract and phosphomycin reduced germ number, levels of leukocyte esterase and urinary procalcitonin in rat model of UTI.